How far west into Asia have Eskimo languages been spoken, and which ones? - Fortescue, Michael (Études/Inuit/Studies, 2004)
AbstractIt has long been suggested by archaeologists that Eskimo-speaking groups were present along the coasts of northeastern Asia much further west than their present confinement to the tip of the Chukotkan Peninsula suggests. However, little linguistic evidence confirming this has been adduced. The pitfalls of misinterpretation of early word-list materials is illustrated with an examination of the facts and non-facts concerning the so-called Anadyr Eskimos supposed to have been met in the early 19th century far to the west, speaking what looks like the Naukanski language of East Cape. With the availability of new data on recently extinct Kerek, it is possible to put together from the hitherto sparse phonological and lexical data a plausible hypothesis that explains, among other things, certain prosodic features of coastal Chukotian languages in terms of a relatively recent Yupik Eskimo substratum all the way to the Kamchatkan isthmus. These features largely coincide with the areas where the original Chukotian vowel harmony system has broken down, in an almost contiguous coastal strip cutting across major language boundaries. This is set within a broader scenario for the spread of successive waves of Eskimo languages on the Asian side, back from their focal area around Bering Strait during successive phases of Neo-Eskimo culture. An explanation of the origin of Yupik rhythmical stress—and its relationship to peculiarities of the highly aberrant Sirenikski language and to the nature of adjacent Chukotian prosodies—will fall out from this scenario.